PENGARUH KECERDASAN EMOSIONAL DAN PENGUASAAN KETERAMPILAN PEMBELAJARAN TERHADAP PRODUKTIVITAS GURU MATA PELAJARAN AKUNTANSI - Murwartiningsih, - (Fakultas Ekonomi, Universitas Negeri Semarang, 2009)
The problem of this research is there any positive influence emotional quotient and learning skill mastering toward teachers productivity in accounting subject in Senior High School Region of Semarang. The result be known that there is an influences between emotional quotient and learning skill toward teachers productivity in senior high school region of Semarang symultan and partial. Based on the result, it is suggested teacher could determine the appropriate model learning, so it can attract the student interest toward the subject. Hope the teacher could create, enrich, maintain and adapt the way to teach to attract and maintain student interest in using time teaching so the learning more effectively and need teacher training revitalization to repair teacher performance in the way to increase professionalism ability and not only to find teachers certification. Key word : Emotional Quotient, Learning ability and Teachers Productivity in accounting subject.